Crimean-Congo Hemorrhagic Fever in European Part of Turkey: Genetic Analysis of the Virus Strains from Ticks and a Seroepidemiological Study in Humans - GARGILI KELEŞ, AYŞEN (MARY ANN LIEBERT, INC, 2011)
A survey of ticks from domestic ruminants, together with a serosurvey in humans was conducted in Thrace (northwestern Turkey) to evaluate the prevalence of Crimean-Congo hemorrhagic fever virus (CCHFV) in ticks and humans. More prevalent ticks were Hyalomma marginatum, Hyalomma aegyptium, Rhipicephalus bursa, and Rhipicephalus (Boophilus) annulatus, with low numbers of Dermacentor marginatus, Rhipicephalus sanguineus group, and Ixodes ricinus. No differences in the tick faunal composition were found among surveyed provinces. CCHFV was detected using specific primers for strains belonging to both Europe 1 and Europe 2 clades in a total of 15 pools of ticks collected in nine localities. The maximum likelihood estimate of infection rate was calculated as 0.72/100 ticks (95% CI = 0.42-1.16). Viral RNA was observed only in H. marginatum, R.(B.) annulatus, and R. bursa with overall maximum likelihood estimate infection rates being 0.93 (95% CI = 0.35-2.05), 0.74 (95% CI = 0.24-1.78), and 1.67 (95% CI = 0.69-3.46), respectively. The surveyed region is the only place where both viral strains are circulating together in nature in Turkey. Results from serosurvey on 193 samples from three localities in the region showed that immunoglobulin M and immunoglobulin G rates are compatible with an epidemiological situation in which the virus has been present for a long time and is not the result of a recent invasive event from the main epidemic center in Anatolia (north-central Turkey). Seropositivity rates cannot be compared against the tick faunal composition, because of the homogeneity in the results about tick surveys. The high rate of seropositivity, and the prevalence of CCHFV in both Europe 1 and 2 clades among the ticks, but few clinical cases suggest that the circulation of both viral strains may confer protection against the CCHFV infection.
Keywords: Crimean-Congo Hemorrhagic Fever; IgG and IgM; Thrace; Viral strains